Parallel design: non-standard mechanical scheme design procedure in parallel manufacturing - LI Shimeng; WANG Fei-Yue (智能科学与技术学报)
Parallel manufacturing is a new manufacturing form in industry, deeply integrating informalization, automation, and AI. In this paper we illustrated the procedure of non-standard mechanical design in parallel manufacturing, claiming it a nested parallel system. We proposed the ACP method based on the standard procedure and the emulated procedure, and defined the social-value-vector and trended-social-value-matrix so as to take the advantage of data in CPSS. We also presented Xinglun robot speed reducer as a case study of non-standard mechanical design in parallel design.